Corrélation entre l’imagerie par résonnance magnétique, l’extemporanée et l’histologie définitive des tumeurs parotidiennes: série de cas - Zouhair, Najib (Pan Afr Med J, 2020)
Parotid gland tumor is complex and poses diagnostic and therapeutic problems. The purpose of this study was to assess the role of extemporaneous examination in the management of patients with parotid gland tumors. We report a pro and retrospective analytical study of a series of cases of salivary gland tumors, whose data were collected in the ENT and in the department of cervical-facial Surgery at the University Hospital in Casablanca, between January 2012 and December 2015. Seventy two cases of parotid tumors were recorded. The sex-ratio (H/F) was 0.94, 0.76 for patients with benign tumors and 1.62 for patients with malignant tumors. The average age was 47 years (15- 75 years). The median of consultation time was 40 months. Clinical symptoms were dominated by parotid swelling (100%), pain in 25% of patients, facial palsy in 6%, and cervical adenopathies in 10%. Ultrasound was recommended in 80% of patients. MRI was performed in 26% of cases. All patients underwent surgery, 76% of patients underwent exofacial parotidectomies and 24% total conservative parotidectomies. This treatment was associated with ganglion resection in 24% of cases and radiotherapy in 24% of cases. Extemporaneous examination was performed in 71% of patients, its susceptibility was 89% and its specificity 88%. Definitive histological diagnosis was confirmed by anatomopathological examination in all cases. We confirmed benign and malignant tumors in 71% and 29% of cases respectively. Benign tumors were dominated by pleomorphic adenoma (59%), while malignant lesions were dominated by mucoepidermoid carcinoma (38%). The postoperative course was marked by: discrete haematoma in 4% of cases, transient facial palsy in 15%, superinfection of the wound in 3% and post-parotidectomy Frey´s syndrome in 3% of patients. One patient had labial recurrence of acinar cell carcinoma. No cases of death were noted. Parotid gland tumors are characterized by a great histological variability. Differentiation between malignant tumor and benign tumor is often difficult. Currently, MRI is the imaging test of choice. Extemporaneous examinationis is very useful intraoperatively when it is necessary to communicate with the pathologist. Multidisciplinary approach is adopted including ENT, oncological, radiotherapeutic, pathological and radiological approaches. Prognosis depends on the histological type, the stage of progression and treatment.